Minimizing Medication Errors from Electronic Prescription Transmission—Digitizing Compounded Drug Preparations - Parrish, Richard H.; Bohannon, Donna; Emrick, Steven P.; Serumaga, Brian; Guharoy, Roy (Pharmacy, 2019)
Lack of standardization related to compounded drug preparations, especially in the transition of care situations, threatens patient safety by facilitating medication error. This paper outlines progress to-date from the United States Pharmacopeia (USP) Expert Panel on the Exchange of Compounded Drug Preparation Information in Health IT Systems. The work plan developed for the group is focused on proposing a set of encoding rules that would govern how compounded nonsterile drug preparations (CNSPs) are digitized and exchanged, including patient electronic health records (EHR), pharmacy systems, e-prescribing (eRx), and other Health IT (HIT) systems to ensure a seamless compounding process tailored to the needs of an individual patient. Included in this work are identifying authorized compounding monographs, surveying provider and end-user groups for information about data specificity during e-prescribing, and generating guidelines for the development of a compatible data model for clinical formulation identifiers (CF-IDs). This paper will also discuss how evolving nomenclature standards for CNSPs within HIT systems are part of a quality assurance system for comprehensive medication management (CMM) in children, thereby minimizing medication errors across the continuum of care. Finally, a network approach for the design of medication management systems for children and their families/caregivers is proposed. Keywords: compounded drug preparation; electronic prescribing; health information technology; interoperability; medication error; systemized nomenclature of medicine
Keywords: compounded drug preparation; systemized nomenclature of medicine; interoperability